(2x - 1)² - (2-3x)²
Passo a passo, ajudaaaa !!!!!!
Soluções para a tarefa
Respondido por
1
Bom dia
(2x - 1)² = (2x - 1)*(2x - 1)
= 4x² - 2x - 2x + 1
= 4x² - 4x +1
(2 - 3x)² = (2 - 3x)*(2 - 3x)
= 4 - 6x - 6x + 9x²
= 9x² - 12x + 4
(2x - 1)² - (2 - 3x)²
= 4x² - 4x +1 - (9x² - 12x + 4)
= 4x² - 4x + 1 - 9x² + 12x - 4
= -5x² + 8x - 3
(2x - 1)² = (2x - 1)*(2x - 1)
= 4x² - 2x - 2x + 1
= 4x² - 4x +1
(2 - 3x)² = (2 - 3x)*(2 - 3x)
= 4 - 6x - 6x + 9x²
= 9x² - 12x + 4
(2x - 1)² - (2 - 3x)²
= 4x² - 4x +1 - (9x² - 12x + 4)
= 4x² - 4x + 1 - 9x² + 12x - 4
= -5x² + 8x - 3
Perguntas interessantes
ENEM,
11 meses atrás
Matemática,
11 meses atrás
Biologia,
11 meses atrás
Ed. Física,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás